PENGARUH MODEL PEMBELAJARAN DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PADA MATAKULIAH POLA KERAH - SOELISTYOWATI . (Serat Rupa: Journal of Design, 2018)
This study aims to get information about the differences in learning outcomes among students who study use the problem-based learning and direct learning on the basis of competence collar pattern making, getting information about the differences in learning outcomes, the students has a learning style of visual, auditory and kinesthetic on the basis of competence collar pattern making, getting information about the interaction between learning models and learning styles to learning outcomes in basic competencies collar pattern making. The research design in this study used a Factorial Design. The sample classes used in this study was a class A and  B Universitas Ciputra Surabaya academic year 2016/2017. Analysis of data using Analysis of Variance (ANOVA) with a significant level of 0,05 to 0,010 significant 2.871.403. This research found that learning outcomes of students who study use the problem-based learning was significantly higher than the students who study use the direct learning on the basis of competence collar pattern making.  Learning outcomes of the students have a learning style of visual was significantly higher than the students has a learning style of auditory and kinesthetic on the basis of competence collar pattern making.  There was an interaction between learning models and learning styles to learning outcomes in basic competencies fashion production collar pattern making.